2021
DOI: 10.1111/tpj.15407
|View full text |Cite
|
Sign up to set email alerts
|

A SNP‐based genetic dissection of versatile traits in bread wheat (Triticum aestivum L.)

Abstract: The continuous increase in global population prompts increased wheat production. Future wheat (Triticum aestivum L.) breeding will heavily rely on dissecting molecular and genetic bases of wheat yield and related traits which is possible through the discovery of quantitative trait loci (QTLs) in constructed populations, such as recombinant inbred lines (RILs). Here, we present an evaluation of 92 RILs in a bi-parental RIL mapping population (the International Triticeae Mapping Initiative Mapping Population [IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 107 publications
3
55
1
1
Order By: Relevance
“…The QTL of plant height, TGW, and grain weight per spike were detected between 598 and 641 Mb on 1B [ 76 ]. The TGW QTL was also reported on 1B.1 [ 55 ] and 1B’s long arm [ 10 ]. An ELF gene ( TaELF3-1B ) was 4 Mb beyond cluster 1B.3 (685.6 Mb), which may contribute to the QTL.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The QTL of plant height, TGW, and grain weight per spike were detected between 598 and 641 Mb on 1B [ 76 ]. The TGW QTL was also reported on 1B.1 [ 55 ] and 1B’s long arm [ 10 ]. An ELF gene ( TaELF3-1B ) was 4 Mb beyond cluster 1B.3 (685.6 Mb), which may contribute to the QTL.…”
Section: Discussionmentioning
confidence: 97%
“…Similar QTL results of TGW and seed width were reported on this region in previous studies [ 10 , 70 , 71 ]. Recently, the QTL of grain weight per spike, GN, grain yield (GY), and TGW were also detected in this region [ 55 ]. The results indicated that this region contributed TGW and seed-related parameters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations